Legal Protection for the Rights of Children Exploited as Beggars - Dwi Kusumawati; Yunas Derta Luluardi (Asian Journal of Law and Humanity, 2023)
Exploitation of children who are used as beggars is an action that is contrary to one of the rights of children that has been regulated in the constitution or law. The basic rules that serve as guidelines for protecting children's rights are the 1945 Constitution article 28B paragraph (2), the Law on Child Welfare, and the Law on Child Protection. This research was taken from the problems of children who become beggars in Pekalongan Regency. By using empirical juridical research with a statutory approach, conceptual approach and qualitative approach. The results of this research are that the legal protection efforts carried out by the Regional Government of Pekalongan Regency only take the form of handling. There are no basic regulations regarding the protection of children who are used as beggars so no legal action has been provided. So there is a need for regional regulations regarding legal protection for children, especially protection for children who are exploited as beggars, so that it becomes the basis for the government in taking policies to provide legal protection for children who are victims of exploitation.